Factors associated with breast self-examination among women of reproductive age - Azkiyaunnisa' Azkiyaunnisa'; Lara Syukma Hara (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast cancer remains a major health problem in Indonesia, with high morbidity and mortality rates. Early detection through breast self-examination (BSE) is essential; however, its practice among women is still low. Purpose: To determine the relationship between knowledge, attitude, and information exposure with BSE practise among women of reproductive age in the working area of Andalas Public Health Center in 2025. Method: This study used a quantitative analytic descriptive design with a cross-sectional approach. A total of 53 respondents were selected using purposive sampling. Data were collected through questionnaires and interviews and analyzed using the chi-square test with a significance level of p<0.05. Results: Most respondents had good knowledge (67.9%), positive attitudes (71.7%), and had been exposed to information (67.9%), yet 54.7% did not perform BSE. There was a significant relationship between knowledge (p=0.013) and attitude (p=0.044) with BSE practice, while information exposure was not significantly associated (p=0.287). Conclusion: Knowledge and attitude are significantly associated with BSE practice, while information exposure is not. Strengthening effective health education is needed to improve awareness and early detection of breast cancer.